The spatial relation between land use and crime - Izatul Yusof; Rosmadi Fauzi (Penerbit Universiti Kebangsaan Malaysia, 2019)
Crime is often associated with social and economic problems. However, studies also showed that land use factor can cause crime. In Malaysia, zoning system is used to manage and administer land use in urban or rural areas. This study was, therefore conducted to measure the spatial distance and the strength of spatial distance between land use and crime. The analysis was done based on motorcycle thefts within a period of three years (2012-2014) in the Federal Territory of Putrajaya. The overlay map and multiple buffer zone techniques in the Geographic Information System (GIS) application were used to determine the spatial distance of land use. Chi Square statistical analysis and the Eta (η) coefficient were used to see the strength of relationship between spatial distance of land use and crime. The results of the analysis showed that there was a significant and strong relationship between land use, spatial distance and motorcycle theft. The analysis indicated that the motorcycle theft incidences were concentrated on a very close distance at commercial, leisure and recreational areas, and residential areas at a distance of between 0m and 150m. In the context of motorcycle thefts, residential and commercial land use have become the generators of motorcycle assets. This situation is also an indirect driving factor for motorcycle thefts. It therefore follows that spatial prevention and control should be given to land use that generates motorcycle assets.